51.5 W monolithic single frequency 1.97 $\rmbmu $m Tm-doped fiber amplifier. (14th February 2014) - Wang, Xiong; Zhou, Pu; Wang, Xiaolin; Xiao, Hu; Si, Lei
Abstract We demonstrate a monolithic single frequency Tm-doped fiber amplifier with output power of 51.5 W. A single frequency fiber laser at 1.97 <alternatives><inline-graphic xlink:href="ark:/27927/pgg4xjjpx1k" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> <![CDATA[$\rmmu $]]> </alternatives>m is amplified by a cascaded master oscillator power amplifier (MOPA) system with all-fiber configuration. The optical-to-optical conversion efficiency of the main fiber amplifier is 45%. No amplified spontaneous emission (ASE) or stimulated Brillouin scattering (SBS) effect is observed in the fiber amplifier. The output power could be further scaled by launching more pump power.